Flaxseed oil (Linum Usitatissimum) attenuates restraint stress-induced depressive-like behavior: Upregulation of neurotrophic factors in CA1 region of hippocampus - Talei, Sahand; Mokhtari, Tahmineh; Asadi, Ilia; Arab, Leila; Hassanzadeh, Negar; Hosseinjani, Emadoddin; Hassanzadeh, Gholamreza (Journal of Contemporary Medical Sciences, 2021)
Objectives: In this study, we aimed to evaluate the anti-depressant effects of FS oil on the depressive-like behavior following immobility stress in mice. Methods: In this study, 32 male mice were divided into four groups: Control group; FS oil group; Model group: The immobility stress (using falcon for 20 day, 6 hours a day) + feeding with normal saline by oral gavage for another 20 days); Model+FS group: The immobility stress + feeding with 0.2 ml/kg of FS oil by oral gavage for another 20 days. At the end, all mice were evaluated with tail suspension test (TST) and sacrificed through cardiac puncture method. The brain was isolated and prepared for molecular and histopathological studies. Results: The gene expression and protein level of BGNF and GDNF were significantly increased in FS oil treated groups (P<0.05). In microscopic evaluations, the number of dead neurons significantly deceased in FS group (P<0.05). TST results showed a significant decrease in immobility time and depressive-like behaviors in FS oil treated group (P<0.05). Conclusion: FS oil feeding may be effective in treatment of depressive like disorders through its anti-oxidative and neurotrophic promoting features. Therefore, it can be used as an appropriate alternative choice in daily diet to prevent depression in clinical investigations.